PENGARUH HARGA, ONLINE CUSTOMER REVIEW DAN FASILITAS TERHADAP TINGKAT HUNIAN DI PT. KARYA CIPTA PESONA (ARYADUTA MEDAN) - Sri Rezeki; Ninie (LPPM STIE EKA PRASETYA, 2019)
The purpose of this study is to determine the effect of the Price, Online Customer Review and Facilities on Occupancy Rate at PT. Karya Cipta Pesona (Aryaduta Medan). The research methodology used is descriptive quantitative method, the unit of analysis in this study is PT. Karya Cipta Pesona (Aryaduta Medan) and its observation unit are guests from PT. Karya Cipta Pesona (Aryaduta Medan). The population in this study were guests from PT. Karya Cipta Pesona (Aryaduta Medan) as many as 61,565 respondents. The technique of determining the number of samples used in this study is the Slovin formula and amounts to 100 respondents. The research method used is by data collection techniques through library research and field research conducted systematically based on research objectives. The analytical method used to solve problems and prove hypotheses is descriptive analysis, regression analysis. This analysis includes validity and reliability, classic assumption test, multiple regression analysis, hypothesis testing through t and F test, and test the coefficient of determination (R2). From the analysis obtained a regression analysis Room Occupancy = 0.004 +0.2286 Price + 0.744 Online Customer Review + 0.271 Facilities + e. The results of the t test show that the price variable has a positive and significant effect on Room Occupancy at PT. Karya Cipta Pesona (Aryaduta Medan) where tcount 3.872 > ttable 1.984, Online Customer Review variable has a positive and significant effect on Room Occupancy at PT. Karya Cipta Pesona (Aryaduta Medan) where tcount 6.910 > ttable 1.984 and Facilities variables have a positive and significant effect on Room Occupancy at PT. Karya Cipta Pesona (Aryaduta Medan) where tcount is 3.753 > ttable 1.984. The results of the F test show that Fcount 61.749 > Ftable 2.70 that means the independent variables Price, Online Customer Review and Facilities simultaneously influence the dependent variable Occupancy. The determination coefficient test results (R2) indicate that 65.90% of Occupancy variables are influenced by Price, Online Customer Review and Facilities variables, while the remaining 34.10% is explained by the influence of other factors or variables outside the model such as Service Quality and Satisfaction.